Tall fescue seed extraction and partial purification of ergot alkaloids - Ji, Huihua; Fannin, F.; Klotz, J.; Bush, Lowell (Frontiers in Chemistry, 2014)
Many substances in the tall fescue/endophyte association (Schedonorus arundinaceus/Epichloë coenophiala) have biological activity. Of these compounds only the ergot alkaloids are known to have significant mammalian toxicity and the predominant ergot alkaloids are ergovaline and ergovalinine. Because synthetically produced ergovaline is difficult to obtain, we developed a seed extraction and partial purification protocol for ergovaline/ergovalinine that provided a biologically active product. Tall fescue seed was ground and packed into several different sized columns for liquid extraction. Smaller particle size and increased extraction time increased efficiency of extraction. Our largest column was a 114 × 52 × 61 cm (W×L×D) stainless steel tub. Approximately 150 kg of seed could be extracted in this tub. The extraction was done with 80% ethanol. When the solvent front migrated to bottom of the column, flow was stopped and seed was allowed to steep for at least 48 h. Light was excluded from the solvent from the beginning of this step to the end of the purification process. Following elution, ethanol was removed from the eluate by evaporation at room temperature. Resulting syrup was freeze-dried. About 80% recovery of alkaloids was achieved with 18-fold increase in concentration of ergovaline. Initial purification of the dried product was accomplished by extracting with hexane/water (6:1, v/v) and the hexane fraction was discarded. The aqueous fraction was extracted with chloroform, the aqueous layer discarded, after which the chloroform was removed with a resulting 20-fold increase of ergovaline. About 65% of the ergovaline was recovered from the chloroform residue for an overall recovery of 50%. The resultant partially purified ergovaline had biological activities in in vivo and in vitro bovine bioassays that approximate that of synthetic ergovaline.